Hypoxia-inducible factor 1 is a basic-helix-loop-helix-PAS heterodimer regulated by cellular O2 tension. - Wang, G L (1995)
Hypoxia-inducible factor 1 (HIF-1) is found in mammalian cells cultured under reduced O2 tension and is necessary for transcriptional activation mediated by the erythropoietin gene enhancer in hypoxic cells. We show that both HIF-1 subunits are basic-helix-loop-helix proteins containing a PAS domain, defined by its presence in the Drosophila Per and Sim proteins and in the mammalian ARNT and AHR proteins. HIF-1 alpha is most closely related to Sim. HIF-1 beta is a series of ARNT gene products, which can thus heterodimerize with either HIF-1 alpha or AHR. HIF-1 alpha and HIF-1 beta (ARNT) RNA and protein levels were induced in cells exposed to 1% O2 and decayed rapidly upon return of the cells to 20% O2, consistent with the role of HIF-1 as a mediator of transcriptional responses to hypoxia.